The ABC costs method and its application in the National University of Chimborazo - Arellano Cepeda, Otto Eulogio (2019)
Objective: To determine how the Activity Based Costing (ABC) method and its application work in determining the real cost of education at the National University of Chimborazo of the Republic of Ecuador. Method: The inductive method is used, at a descriptive - causal level. The survey was applied to obtain the information of a sample of 56 workers between teachers and administrators staff of a total population of 745 people. Results: The results show that the application of a cost-per-activity system reduces procedures and improves accounting of the activities related to management, teaching and research in an appropriate manner. It is an efficient model that can be applied in Higher Education Institutions. Conclusions: The Activity-Based Costs method (ABC) can be consider as an efficient model that allows to know the real costs of the academic services offered by the University and allows the making of corrective and investment decisions in the improvement of the educational quality; Also can be applied in all Higher Education Institutions of Ecuador and Educational character.